Las franquicias en el Ecuador y su aplicación en la ciudad de Babahoyo como herramienta de desarrollo económico caso de aplicación rikoko - Zúñiga, Mariuxi (2009)
This paper presents the introduction to the market town of Babahoyo Ecuadorian RIKOKO franchise. Doing a thorough market research we can conclude that it is feasible or not the introduction of this franchise. We use surveys of a sample of the inhabitants of the City of Babahoyo to know their preferences, likes, because as its name suggests RIKOKO are responsible for the sale of coconut water carts in the street. In this way infer that the people wanted something new to be cool, so we studied the costs, benefits of the franchise by all Ecuadorian financial study, namely by calculating the initial investment costs, the costs of the projects, the hand workforce, quality control, life and salvage value, the analysis of environmental impact, sales would have, where supply of raw materials, cash flows, sensitivity analysis, feasibility through private calculate the Internal Rate of Return (IRR), Net Present Value (NPV) and the recovery period Discounted (Payback), and concluded that if it is profitable to introduce RIKOKO as would be the first franchisee of drinks in the City, as the main obstacle is that we had more people flocked to the city of Guayaquil to make purchases and in turn exploited for a walk and cool off in the family.